1997
DOI: 10.1017/s0022112097005934
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of Coulomb-driven convection in insulating liquids

Abstract: Electroconvection in a layer of liquid subjected to unipolar injection is characterized by two stability criteria, a linear and a nonlinear one, with an associated hysteresis loop. Experimentally it is found that the velocity field fluctuates around its mean value. A temporal analysis of the measured current, which is directly related to the velocity, revealed the existence of a well-defined frequency correlated to the mean rotation time of a fluid particle in the convective cell, thus ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
78
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 0 publications
11
78
1
Order By: Relevance
“…For higher values of T, the peaks progressively broaden until the whole spectrum becomes broadband for T > 5000. Our findings present some differences from the results obtained by Chicón et al 7 and Vázquez et al 9 Chicón et al found a broadband spectrum for L = 0.614. In Ref.…”
Section: E Spectral Analysiscontrasting
confidence: 99%
See 2 more Smart Citations
“…For higher values of T, the peaks progressively broaden until the whole spectrum becomes broadband for T > 5000. Our findings present some differences from the results obtained by Chicón et al 7 and Vázquez et al 9 Chicón et al found a broadband spectrum for L = 0.614. In Ref.…”
Section: E Spectral Analysiscontrasting
confidence: 99%
“…3 The overall hysteretic behaviour is depicted in Figure 11. This hysteresis loop is similar to the one obtained by Figure 10 of Chicón et al 7 In particular, the value of the velocity amplitude at the linear criterion is close to 3. The hysteresis loop for lateral walls is indicated in Figure 12(a).…”
Section: B Nonlinear Criterionsupporting
confidence: 89%
See 1 more Smart Citation
“…Several attempts to model numerically the development of EHD flows and especially electro-convective flows have been made in the past. But most of the authors started their computations from an assumed velocity field and not from a real resolution of the Navier-Stokes equations [15]. In [16] the appropriate electrodynamics equations coupled with the full Navier-Stokes equations are solved numerically with the help of an efficient finite volume method to study the flow structure of EHD plumes.…”
mentioning
confidence: 99%
“…The linear t hreshold for st rong inject ion above which roll st ruct ures arise has been determined through these simulations to be equal to T C 170, whereas [38] quot e T C 171 and [20] quot e T C 163. Below this threshold, t he charge distribution is de ned t hrough an analyt ical expression.…”
Section: Solut Ion Validat Ion: Fr Ee Convect Ion R Oll St R Uct Ur Esmentioning
confidence: 99%